2016
DOI: 10.1007/s11356-016-7701-2
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of NO/NO2 gas injected into a 10-m3 experimental chamber

Abstract: This paper investigates a new test method to assess the photocatalytic activity of plasterboards coated with a TiO dispersion under real-world conditions. The degradation of nitrogen oxides NO (NO and NO) is studied and the photocatalytic efficiency under UV illumination is evaluated in a 10-m room after a constant gas injection. Two ultrafine TiO dispersions are used: 0.85% TiO and 5% TiO, and three types of gas are tested: an NO/NO mixture (8/8 mol-ppm), NO (45 mol-ppm) and NO (45 mol-ppm). The test method p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…In fact, no significant difference was noticed between tests carried out with and without photocatalytic material on the walls. This observation is in accordance with research work reported in the literature showing that NO has no adsorption properties (Maggos et al 2007;Maggos et al 2008;Hot, Martinez et al 2017). The NO and NO 2 concentrations obtained over 240 min in the dark are given in Figure 6.…”
Section: Nox Concentrations Without Photocatalysissupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, no significant difference was noticed between tests carried out with and without photocatalytic material on the walls. This observation is in accordance with research work reported in the literature showing that NO has no adsorption properties (Maggos et al 2007;Maggos et al 2008;Hot, Martinez et al 2017). The NO and NO 2 concentrations obtained over 240 min in the dark are given in Figure 6.…”
Section: Nox Concentrations Without Photocatalysissupporting
confidence: 92%
“…However, experiments carried out under such conditions are not very realistic representations of actual applications, where photocatalytic coatings are applied on large existing surfaces, and some authors have worked on this problem. Assessing PCO efficiency towards air pollution under real-world conditions is a tricky task and only a few studies on this subject have been published so far (Maggos et al 2007;Maggos et al 2008;Gallus et al 2015;Hot, Martinez, et al 2017;Chen & Chu 2011;Crain et al 2016;Horgnies et al 2015;Guerrini 2012). Moreover, only a handful of them are related to indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…DtoxGuard R Int coating was also used in a previous study, in which it was applied to the walls (a surface of 9.3 m 2 was covered) in a 10-m 3 experimental chamber. The authors reported high NO degradation rates under UV and visible light [37,38] .…”
Section: Likelihood Analysismentioning
confidence: 99%
“…. ) [34][35][36][37][38]. Regarding bacterial and fungal disinfection, research has mainly focused on the efficiency of photocatalytic TiO 2 particles used alone, powdered or immobilized in the form of thin film coatings by complex processes (usually involving calcination).…”
Section: Introductionmentioning
confidence: 99%